2015
DOI: 10.1134/s1990747814040023
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydrolysable tannins on native and artificial biological membranes

Abstract: Effects of hydrolysable tannins on plasma membranes of Chara corallina giant cells and lipid bilayer membrane (BLM) were studied. Tannin inhibited chloride channels of alga cell membranes in a dose dependent manner. Current jumps emerging in BLM in the presence of tannin suggest formation of ion chan nels, predominantly anion selective. The presence of cholesterol in BLM increased the open state lifetime of the channels. The findings indicate that hydrolysable tannins possess a membrane activity and are capabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
3
0
1
Order By: Relevance
“…From a molecular standpoint, hydrolysable phenols are polyesters with a sugar core to which many phenolic compounds (mainly phenolic acids) are attached to while proanthocyanidins are polymeric flavan‐3‐ols and both can be hydrolysed with diluted acids (Reed et al ., ; Hartzfeld et al ., ); both bounded‐phenolic compounds are poorly hydrolysed under gastrointestinal conditions in vitro . Nevertheless, hydrolysable phenols and proanthocyanidins can perform relevant bioactivities at gastrointestinal level such as opening anion channels in cell membranes (Borisova et al ., ), enhancing antioxidant capacity at lumen (Jian et al ., ) or can be hydrolysed and metabolised by bacterial enzymes in the large bowel (Velderrain‐Rodríguez et al ., ; Campos‐Vega et al ., )…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From a molecular standpoint, hydrolysable phenols are polyesters with a sugar core to which many phenolic compounds (mainly phenolic acids) are attached to while proanthocyanidins are polymeric flavan‐3‐ols and both can be hydrolysed with diluted acids (Reed et al ., ; Hartzfeld et al ., ); both bounded‐phenolic compounds are poorly hydrolysed under gastrointestinal conditions in vitro . Nevertheless, hydrolysable phenols and proanthocyanidins can perform relevant bioactivities at gastrointestinal level such as opening anion channels in cell membranes (Borisova et al ., ), enhancing antioxidant capacity at lumen (Jian et al ., ) or can be hydrolysed and metabolised by bacterial enzymes in the large bowel (Velderrain‐Rodríguez et al ., ; Campos‐Vega et al ., )…”
Section: Resultsmentioning
confidence: 99%
“…From a molecular standpoint, hydrolysable phenols are polyesters with a sugar core to which many phenolic compounds (mainly phenolic acids) are attached to while proanthocyanidins are polymeric flavan-3-ols and both can be hydrolysed with diluted acids (Reed et al, 1982;Hartzfeld et al, 2002); both bounded-phenolic compounds are poorly hydrolysed under gastrointestinal conditions in vitro. Nevertheless, hydrolysable phenols and proanthocyanidins can perform relevant bioactivities at gastrointestinal level such as opening anion channels in cell membranes (Borisova et al, 2015), enhancing antioxidant capacity at lumen (Jian et al, 2009) or can be hydrolysed and metabolised by bacterial enzymes in the large bowel (Velderrain-Rodr ıguez et al, 2014;Campos-Vega et al, 2015) In this study, the content nonextractable phenolic compounds ranged from 2.1 to 11.5 mg GAE (hydrolysable phenols) to 0.06-0.36 mg CyE (proan- thocyanidins) per gram (Table 1), being blackberry (11.5 mg GAE) and blueberry (0.36 mg CyE) the richest sources of hydrolysable phenols and proanthocyanidins respectively, in agreement with previous reports from other authors (Hager et al, 2008). According to Table 2, hydrolysable phenols modestly correlated with extractable phenols (r = 0.45; P < 0.05) and proanthocyanidins (r = À0.54; P < 0.01), while proanthocyanidins just did with anthocyanins (r = 0.62; P < 0.001).…”
Section: Profile Of Phenolic Compoundsmentioning
confidence: 99%
“…Recently, researches carried out by scientists of Bioorganic Chemistry of the Academy of Sciences of Uzbekistan, have shown prosperity of use of natural phenolic compounds as an antiviral, antioxidant, anti-tumor agents [14][15][16][17][18][19][20]. It was found that these compounds have high biological activity, which manifests itself in suppressing the activity of various viral infections, redox enzymes and etc.…”
Section: Resultsmentioning
confidence: 99%
“…за счёт большого количества гидроксильных групп формирует прочные химические связи с различными биополимерами и осаждает многие белки, что в целом уплотняет и стабилизирует клеточную мембрану. В конечном итоге под действием танина изменяется осмотическая резистентность, а также скорость оседания эритроцитов и увеличивается уровень их агглютинабельности [13].…”
Section: Introductionunclassified